Hubungan Keteraturan Pemakaian Kelasi Besi Dengan Kualitas Hidup Anak Penyandang Thalassemia - Indriyani Ramadhanti; Iin Patimah; Engkus Kusnadi (Jurnal Medika Cendikia, 2021)
Thalassemia is a condition in which a person has a genetic blood disorder characterized by deficiency of the globin chain in hemoglobin. The problem that arises in people with thalassemia is non-compliance in taking iron chelation therapy drugs. Thalassemia as a chronic, lifelong disease requires continuous treatment and treatment, one of which is iron chelation therapy. Iron chelation therapy is able to get rid of the buildup of iron in the body as a result of routine blood transfusions through feces and urine. So that the regular use of iron chelation therapy can affect the quality of life of people with thalassemia. The purpose of this study was to determine the relationship between regular use of iron chelation and quality of life in children with thalassemia in dr. Slamet Garut. The research method used is descriptive analytic using a quantitative approach with the correlation study research design. The sample was calculated based on a correlative research formula totaling 44 people using purposive sampling technique. The results showed that more than half of the respondents (81.6%) did not regularly perform iron chelation therapy, and more than half of the respondents (54.5%) had poor quality of life. There is a significant relationship between regular use of iron chelation and quality of life in children with thalassemia, with a p value = 0.014. So it can be concluded that there is a positive relationship between regular use of iron chelation and quality of life in children with thalassemia at the Dr. Slamet Garut Regional Hospital in 2016. Based on the results of this study, it is recommended that people with thalassemia, especially parents, regularly carry out iron chelation therapy in order to improve the health status and quality of life of children